Studying molecule-surface interactions using magnetically manipulated molecular beams - YOSEF ALKOBY (2022)
Molecular beam techniques contribute crucial knowledge for a wide range of research fields and applications[1, 2]. The goal of this PhD thesis is to contribute to the development of the new magnetic molec-ular interferometry technique and use it to study fundamentally im-portant molecule-surface systems in their ground state. The thesis describes both surface scattering experiments and the development of new instrumentation and experimental methods which make this technique more powerful and insightful. The development, character-isation and testing of a new direct beam line, capable of magnetically analysing the molecular beam without scattering from a surface, is presented. This new addition to the instrument enables gathering important information about the composition and properties of the molecular beam and its response to magnetic fields. This type of infor-mation will be particularly crucial when extending the interferometry technique to molecules where the magnetic Hamiltonian is not well known. Scattering experiments of hydrogen beams from graphene, copper and salt surfaces were performed, gaining unique quantum in-formation about the scattering process. Using magnetic manipulation, we can characterise the different quantum rotational projection states of the molecules before and after scattering from a surface and detect subtle changes in the quantum state during the scattering event.Both the scattering and the direct beam experiments presented in the thesis, were analysed by solving the magnetic evolution quantum mechanically. The results show that the scattering of hydrogen from a lithium-fluoride (001) surface into different diffraction channels, is highly dependent on the rotational projection states, i.e. the orien-tation of the molecular rotation of the incident molecules. In con-trast, the specular scattering of flat copper, Cu(111), and graphene surfaces shows no obvious change in the rotational state populations upon scattering. Further helium and deuterium beams experiments are presented, enhancing our understanding of the molecular magnetic interferometer and validating our analysis methods.